(untitled) (UNED Research Journal, 2021)
Introduction: Participatory research and environmental education initiatives exist in the AmistOsa biological corridor, Costa Rica, but an integration of these community-based processes is not yet clear. Objective: To propose and test a conceptual framework that integrates participatory research with environmental education Methods: We consulted the community to identify fauna and its threats; produced a curriculum for children; and developed a communication strategy. Results: We identified 19 vertebrate species threatened by hunting, deforestation, and others. We produced and tested an educational program adapted to the context of 14 local schools. We are currently developing communication skills to reach both children and researchers (e.g. photography workshops). Conclusion: The results of this approach are satisfactory and could be applied to other communities in the AmistOsa Biological Corridor.